2023
DOI: 10.3998/mpub.11691056
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Damage

Abstract: Collateral Damage provides an overview of how political communication influences the process of incorporation with the broad society as well as its political parties. Sean Richey shows that how politicians talk about immigrants affects how their children perceive America and their feelings about the nation. These perceptions and feelings in turn greatly influence the children’s desire to incorporate into American political society. He also shows that regardless of a speaker’s intended outcome, what is said can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…To our knowledge, this is the first experimental evidence that concerns about the deportation of friends or family members affects U.S.-born Latines' feelings about U.S. immigration policy. In the real world, a variety of factors can make deportation concerns salient, including anti-immigrant rhetoric by prominent politicians (Abrego, 2019;Asad, 2020;Jones et al, 2021;Richey, 2023) and increased attention to deportation and detention by immigration activists (White, 2016). We found, second, that anger, fear, and identity conflict were all independently associated with greater willingness to engage in collective action for immigrants' rights.…”
Section: Discussionmentioning
confidence: 65%
“…To our knowledge, this is the first experimental evidence that concerns about the deportation of friends or family members affects U.S.-born Latines' feelings about U.S. immigration policy. In the real world, a variety of factors can make deportation concerns salient, including anti-immigrant rhetoric by prominent politicians (Abrego, 2019;Asad, 2020;Jones et al, 2021;Richey, 2023) and increased attention to deportation and detention by immigration activists (White, 2016). We found, second, that anger, fear, and identity conflict were all independently associated with greater willingness to engage in collective action for immigrants' rights.…”
Section: Discussionmentioning
confidence: 65%
“…To our knowledge, this is the first experimental evidence that concerns about the deportation of friends or family members affects U.S.-born Latines’ feelings about U.S. immigration policy. In the real world, a variety of factors can make deportation concerns salient, including anti-immigrant rhetoric by prominent politicians (Abrego, 2019; Asad, 2020; Jones et al, 2021; Richey, 2023) and increased attention to deportation and detention by immigration activists (White, 2016). Second, we found that anger, fear, and identity conflict were all independently associated with greater willingness to engage in collective action for immigrants’ rights.…”
Section: Discussionmentioning
confidence: 99%